Stochastic heating of electrons in capacitive RF discharges by plasma oscillations - Manuilenko, O.V. (Вопросы атомной науки и техники, 2012)
Stochastic heating of electrons by plasma oscillations excited in the capacitive discharge plasma is investigated theoretically. We have obtained criteria, when the stochastic heating take place, and demonstrated numerically that this heating mechanism can be sufficiently effective. Изучен стохастический нагрев электронов плазменными колебаниями, возбужденными в плазме емкостного разряда. Получены условия, при которых стохастический нагрев имеет место и показано численно, что такой механизм нагрева может быть достаточно эффективным. Досліджено стохастичне нагрівання електронів плазмовими коливаннями, які збуджено в плазмі ємкісного розряду. Одержано умови, при яких стохастичне нагрівання має місце і показано чисельно, що зазначений механізм нагріву може бути досить ефективним.